1997
DOI: 10.3354/meps154053
|View full text |Cite
|
Sign up to set email alerts
|

Observer effects and training in underwater visual surveys of reef fishes

Abstract: Visual survey techniques are used widely to estimate abundances of target organisms in terrestrial and aquatic environments. There are a number of methodological 'errors' in almost all applications of visual surveys. Given the dependence of all visual survey data on the skill and technique of the observer, one potentially important source of imprecision andlor bias is vanation among and within observers. In studies involving large amounts of fieldwork over great geographic range and many years, it is inevitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 18 publications
4
107
0
Order By: Relevance
“…As discussed by Brock (1982), dwarf, cryptic and nocturnal species are underestimated by the visual census technique. The visual census technique is widely applied and accepted for fish ecological studies on coral reefs (English et al 1994), although differences in skill and technique of observers can be a source of imprecision and/or bias (Thompson and Mapstone 1997). Therefore the first author (M.A.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed by Brock (1982), dwarf, cryptic and nocturnal species are underestimated by the visual census technique. The visual census technique is widely applied and accepted for fish ecological studies on coral reefs (English et al 1994), although differences in skill and technique of observers can be a source of imprecision and/or bias (Thompson and Mapstone 1997). Therefore the first author (M.A.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors suggested that the variability between divers confounded the analysis of diving census data (Thompson and Mapstone 1997). In this study the variation between the 2 divers was tested and found not to be significantly different (except for C. maenas in October) and to be relatively low (Table 6) compared to the variability between sampling dates.…”
Section: Discussionmentioning
confidence: 99%
“…Both can be problematic. Training appears to be an effective way to reduce observer bias, at least for some taxa, but probably has less impact on inherent variability within observers' counts (Thompson & Mapstone 1997). It seems plausible that experience level might also be a factor affecting inter-or intra-observer variability (Kulbicki & Sarramegna 1999), but we are not aware of any previous study which has specifically examined this issue.…”
Section: Introductionmentioning
confidence: 89%